Left Ventricular Myocardial Perfusion before Contrast Pool in Ventricular Cavity in Cardiac MRI in Adult Type Anomalous Left Coronary Artery from Pulmonary Artery with Pulmonary Hypertension - Birardar, Basavaraj; Valakkada, Jineesh; Ayappan, Anoop; Karamakar, Deepmala; Sasidharan, Bijulal (Indian Journal of Radiology and Imaging, 2025)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital coronary anomaly. It has two types, infant and adult types, each with different clinical manifestations and prognosis. Here we report an adult type of ALCAPA syndrome presenting with recurrent syncope and diagnosed as dilated cardiomyopathy with pulmonary hypertension on echocardiography. Cardiac magnetic resonance imaging (MRI) was able to establish ischemia as the cause of dilated cardiomyopathy and raised the suspicion of ALCAPA. Computed tomography (CT) coronary angiogram subsequently confirmed the anomalous origin of the left coronary artery from the main pulmonary artery with right to left shunting due to pulmonary artery hypertension. Viability assessment on cardiac MRI provides additional information for treatment planning. This case highlights the importance and subtle markers in cardiac MRI for ALCAPA presenting with atypical clinical presentation.
Keywords: ALCAPA; cardiac MRI; PAH; perfusion abnormality